Effectiveness Study and Analysis of Infographics in Promoting Cancel Culture Awareness among Batam City Young Generations - Infrisanti Wilson Tong; Jimmy Pratama (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
Cancel culture has emerged and often appears on social media and has become a form of social phenomenon. Cancel culture itself has also emerged in Indonesia and is used as a form of protest and ostracism against public figures who commit social deviations on social media. As a country with a large number of digital natives, having an understanding of cancel culture can help us use social media wisely. Therefore, the author designed an infographic in the form of a motion graphic regarding the meaning of cancel culture. This is supported with the findings of the study by (Oktanizar & Kurniawan, 2021), which suggest that motion graphics can be an effective educational tool for promoting the shipping industry. Specifically, the study showed that the use of motion graphics in promoting the industry using the EPIC (Engagement, Persuasion, Information, and Call-to-Action) model resulted in increased awareness and interest in the shipping industry among the participants. This implies that the use of motion graphics in promoting complex topics such as cancel culture can be an effective strategy to engage and inform audiences. Furthermore, the EPIC model used in the study can serve as a useful framework for designing effective motion graphics for educational purposes. The author uses the ADDIE method and Adobe After Effects software in creating the motion graphic. The author then assesses the level of effectiveness in the media using the EPIC rate method. The results obtained from this study is that the motion graphic media uploaded on Youtube and are classified as effective.